High‐expression β1 adrenergic receptor/cell membrane chromatography method based on a target receptor to screen active ingredients from traditional Chinese medicines. Issue 3 (23rd December 2013) - Yue, Yuan; Xue, Hui; Wang, Xin; Yang, Qian; Song, Yanhong; Li, Xiaoni
Abstract : β‐Adrenergic receptors are important targets for drug discovery. We have developed a new β1 ‐adrenergic receptor cell membrane chromatography (β1 AR‐CMC) with offline ultra‐performance LC (UPLC) and MS method for screening active ingredients from traditional Chinese medicines. In this study, Chinese hamster ovary‐S cells with high β1 AR expression levels were established and used to prepare a cell membrane stationary phase in a β1 AR‐CMC model. The retention fractions were separated and identified by the UPLC–MS system. The screening results found that isoimperatorin from Rhizoma et Radix Notopterygii was the targeted component that could act on β1 AR in similar manner of metoprolol as a control drug. In addition, the biological effects of active component were also investigated in order to search for a new type of β1 AR antagonist. It will be a useful method for drug discovery as a leading compound resource.